Justice League. Season one [videorecording (DVD)]. (DC Comics classic collection., 2006)
Superman, Batman, Wonder Woman, The Flash, Green Lantern, Martian Manhunter, and Hawkgirl unite to become the Justice League. These 26 adventures feature battles with villains and triumphant tales of teamwork that will enthrall and inspire!